A participação contemporânea organizada durante transmissões ao vivo : a interferência no produto final televisivo - Ceratti, Jerônimo Silvello (2021)
This research seeks to understand how contemporary participations organized during live broadcasts occur when there is interference in the final television product, which is the script of a program or the programming as a whole. The work has as corpus the “Craque do Jogo”, by Rede Globo, which represents the phenomenon researched from the Case Study (YIN, 2015) and Netnography (FRAGOSO; RECUERO; AMARAL, 2011). It’s understood that technology, through cyberspace, the internet, mobile internet and smartphones, has enhanced interactivity (PRIMO, 2003), increasing the human being's desire to participate (BORDENAVE, 1983), making the “culture of participation ”(SHIRKY, 2011) even more present in society and generating a phenomenon of organized contemporary participation with the ability to interfere in traditional media such as open television. We believe that the result of this work is not decisive, but applicable to other television products that contain, in essence, public participation.